Prospective, single-centre, randomised controlled trial to evaluate the efficacy and safety of ischaemia-free liver transplantation (IFLT) in the treatment of end-stage liver disease. Issue 5 (5th May 2020) - Huang, Changjun; Huang, Shanzhou; Tang, Yunhua; Zhao, Qiang; Wang, Dongping; Ju, Weiqiang; Yang, Lu; Zhang, Jian; Wu, Linwei; Chen, Maogen; Zhang, Zhiheng; Zhu, Zebin; et al.
Abstract : Introduction: During conventional liver transplantation (CLT), ischaemia-reperfusion injury (IRI) is inevitable and is associated with complications such as early allograft dysfunction (EAD), primary non-function and ischaemic-type biliary lesions. We have established a novel procedure called ischaemia-free liver transplantation (IFLT). The results from a pilot study suggest that IFLT might prevent IRI and yield better transplant outcomes than CLT. The purpose of this study was to further assess the efficacy and safety of IFLT versus CLT in patients with end-stage liver disease. Methods and analysis: This is an investigator-initiated, open-label, phase III, prospective, single-centre randomised controlled trial on the effects of IFLT in patients with end-stage liver disease. Adult patients (aged 18–75 years) eligible for liver transplantation will be screened for participation in this trial and will be randomised between the IFLT group (n=34) and the CLT group (n=34). In the IFLT group, the donor liver will be procured, preserved and implanted with continuous normothermic machine perfusion (NMP). In the CLT group, the donor liver will be procured after a fast cold flush, preserved in 0°C–4°C solution and implanted under hypothermic and hypoxic conditions. Patients in both groups will be managed according to the standard protocol of our centre. The primary end point is the incidence of EAD after liver transplantation. Intraoperative and postoperative parameters of donor livers and recipients will be observed and recorded, and postoperative liver graft function, complications and recipient and graft survival will be evaluated. After a 12-month follow-up of the last enrolled recipient, the outcomes will be analysed to evaluate the safety and efficacy of IFLT versus CLT in patients with end-stage liver disease. Ethics and dissemination: The protocol was reviewed and approved by the Ethics Committee of The First Affiliated Hospital of Sun Yat-sen University. The findings will be disseminated to the public through conference presentations and peer-reviewed scientific journals. Trial registration number: ChiCTR1900021158.